2016
DOI: 10.1017/s0025315415002209
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Blue Gym’: What can blue space do for you and what can you do for blue space?

Abstract: The Blue Gym Initiative was created in the UK in 2009 to explore: (1) whether blue space environments might be positively related to human health and well-being; and (2) whether the public could be encouraged to preserve and protect these environments. Whilst the wider initiative considers all blue spaces including inland bodies of water (e.g. lakes, rivers and canals as well as the coasts and oceans), to date the focus has been primarily on marine and coastal environments. In this paper, we provide a brief hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 52 publications
1
38
0
3
Order By: Relevance
“…A survey conducted by the non‐governmental organization (NGO) Sustainable Surf and the University of Plymouth shows that, of 500 respondents, 84% indicated that surfing raises their environmental awareness, due to both their greater level of connection with nature and their direct confrontation with negative human impacts on the ocean, such as pollution (Sustainable Surf, ). White et al’s () Blue Gym group mentions a number of studies that show a link between time spent in marine environments and higher propensity for environmental activism, with this being a primary focus for future research by the group.…”
Section: The Conservation Value Of Surf Breaksmentioning
confidence: 99%
“…A survey conducted by the non‐governmental organization (NGO) Sustainable Surf and the University of Plymouth shows that, of 500 respondents, 84% indicated that surfing raises their environmental awareness, due to both their greater level of connection with nature and their direct confrontation with negative human impacts on the ocean, such as pollution (Sustainable Surf, ). White et al’s () Blue Gym group mentions a number of studies that show a link between time spent in marine environments and higher propensity for environmental activism, with this being a primary focus for future research by the group.…”
Section: The Conservation Value Of Surf Breaksmentioning
confidence: 99%
“…Neuropsychology, neuroeconomics and neuroconservation are areas to watch for emerging themes and breakthrough insights within this category, as applications of neuroimaging technology become more viable. Studies of the cognitive, emotional, psycho-logical, social, and spiritual value of access to 'blue space', wildlife, and biodiversity will begin to include sea turtles, their habitat, and conservation projects (Kuo 2015, Cracknell et al 2016, White et al 2016.…”
Section: Q11 What Constitutes a Healthy Turtle?mentioning
confidence: 99%
“…They influence travel and tourism sectors (Houston, 2008) as well as the well-being of local residents due to the availability of low-cost recreational areas (Ashbullby et al 2013, Wheeler et al 2012, White et al 2016). In October 2000, the U.S. Environmental Protection Agency (EPA) established the Beaches Environmental Assessment and Coastal Health (BEACH) Act (U.S.…”
Section: Introductionmentioning
confidence: 99%